(untitled) (Research, Society and Development, 2022)
Objective: This research evaluated the cardiovascular risk of patients with periodontal disease, according to their different levels of severity, comparing them with healthy periodontal patients. Methodology: The research was carried out with patients from the Clínica Escola Odontológica da UFCG, campus Patos-PB, being divided into the groups Periodontal Disease (PD) and Control Group (CG). The DP group was subdivided into patients with Gingivitis, Localized Periodontitis and Generalized Periodontitis. Blood samples were collected for analysis of serum levels of C-Reactive Protein (CRP), using the ultra-sensitive method. Results: Of the 66 participants, it was found that the majority were female (54,54%). The mean age was 32,37 ± 2,41 years for the DP group and 24,08 ± 1,74 years for the CG. Serum CRP levels were higher in Group DP (6,09 ± 1,34 mg/l; n = 30) when compared to CG (2,21 ± 0,23 mg/l; n = 36). The subgroups with Gingivitis (6,95 ± 1,99 mg/l; n = 22) and with Localized Periodontitis (11,82 ± 5,27mg/l; n = 5) had CRP values ​​significantly higher than those of the CG (2,21 ± 0,23 mg/l; n = 36). There were no differences between the values ​​of the group with Generalized Periodontitis (2,98 ± 1,63 mg/l; n = 3) compared to the control group. Conclusion: It was concluded that patients with periodontal disease had higher levels of CRP when compared to patients of the healthy periodontium, statistically supporting a greater propensity for the development of heart diseases by individuals with periodontopathies.